Implementasi Pendidikan Karakter melalui Media E-Cling (Edugame Cinta Lingkungan) pada Kelas 4 Tema 3 Subtema 3 di SDN 02 Pangongangan - Nunung Dwi Lestari; Hartini Hartini; Nur Samsiyah (Prosiding Konferensi Ilmiah Dasar, 2022)
The process of character education with the environment has a close and inseparable relationship. Therefore, the school environment is a good place for education for the growth of the character of students. One of the characters that is currently being carried out and developed by schools is character education that cares for the environment. Therefore, the role of the individual in the environment is very influential with the state of the environment. The research method used is descriptive qualitative with data collection namely observation, interviews and documentation. The purpose of this study was to find out how the implementation of character education through the media of E-Cling (environmental love edugame) in grade 4 theme 3 sub-theme 3 at SDN 02 Pangongangan. The results of this study indicate that the student character values obtained from the edugame learning activities that have been carried out are in the form of discipline, environmental care and responsibility.